Gluhend Tiles Enterprise / Ahmad Danial Ahmad Supian...[et. al] - Ahmad Supian, Ahmad Danial; Abdul Hamid, Hasan; Fuat, Muhammad Amirul Hakim; Mohd Zailani, Nur Fatin Nabila; Abdul Hamid, Nur Nabilah Nazrah (2019)
This business plan is our proposal present as overview of business description. This includes activities and goals for our glowing tiles within three (3) years of business operation. Gluhend Tiles Enterprise Company starts operating at Jalan Adda 3/1, Adda Height. This is because the location is more strategic since it is a developing city and has a high tendency on getting high demand of purchases. As for our mission, we are targeting to expand our market share within three (3) years and our brand will be everyone's choice within IO years. Our glowing tiles are not only can be installed with a purpose for decoration, but it can also be used as safety precautions as it can help people on stepping on the right position such as on stairs. As for our vision, we target to be a world-renowned tiles company in the region and fulfil the needs of the market demand while the customer's satisfaction becomes our priority. Gluhend Tiles Enterprise operates at Jalan Adda 3/1 for 12 hours from Saturday until Thursday starts at 10 am and finished at 10 pm. We are already ensured that our product can help on making a building looks more iconic at night.